Autoreactive Plasmablasts After B Cell Depletion With Rituximab and Relapses in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 5 (15th March 2023) - Berti, Alvise; Hillion, Sophie; Konig, Maximilian F.; Moura, Marta Casal; Hummel, Amber M.; Carmona, Eva; Peikert, Tobias; Fervenza, Fernando C.; Kallenberg, Cees G.M.; Langford, Carol A.; Merkel, Peter A.; Monach, Paul A.; et al.
Abstract : Objective: Autoreactive B cells are responsible for antineutrophil cytoplasmic antibody (ANCA) production in ANCA‐associated vasculitis (AAV). Rituximab (RTX) depletes circulating B cells, including autoreactive B cells. We aimed to evaluate changes and associations with relapse of the circulating autoreactive B cell pool following therapeutic B cell depletion in AAV. Methods: Sequential flow cytometry was performed on 148 samples of peripheral blood mononuclear cells from 23 patients with proteinase 3 (PR3)–ANCA–positive AAV who were treated with RTX for remission induction and monitored after stopping therapy during long‐term follow‐up in a prospective clinical trial. PR3 was used as a ligand to target autoreactive PR3‐specific (PR3+) B cells. B cell recurrence was considered as the first blood sample with ≥10 B cells/μl after RTX treatment. Results: At B cell recurrence, PR3+ B cell frequency among B cells was higher than baseline ( P  < 0.01). Within both PR3+ and total B cells, frequencies of transitional and naive subsets were higher at B cell recurrence than at baseline, while memory subsets were lower ( P  < 0.001 for all comparisons). At B cell recurrence, frequencies of B cells and subsets did not differ between patients who experienced relapse and patients who remained in remission. In contrast, the plasmablast frequency within the PR3+ B cell pool was higher in patients who experienced relapse and associated with a shorter time to relapse. Frequencies of PR3+ plasmablasts higher than baseline were more likely to be found in patients who experienced relapse within the following 12 months compared to those in sustained remission ( P  < 0.05). Conclusion: The composition of the autoreactive B cell pool varies significantly following RTX treatment in AAV, and early plasmablast enrichment within the autoreactive pool is associated with future relapses.